All the lonely people - Gayle, Mike (Grand Central Publishing, 2021)
"Life is waiting to happen to Hubert Bird. But first he has to open his front door and let it in. In weekly phone calls to his daughter in Australia, widower Hubert Bird paints a picture of the perfect retirement, packed with fun, friendship, and fulfilment. But he's lying. The truth is day after day drags by without him seeing a single soul. Until he receives some good news - good news that in one way turns out to be the worst news ever, news that will force him out again, into a world he has long since turned his back on. Now Hubert faces a seemingly impossible task: to make his real life resemble his fake life before the truth comes out. Along the way Hubert stumbles across a second chance at love, renews a cherished friendship, and finds himself roped into an audacious community scheme that seeks to end loneliness once and for all . . . Life is certainly beginning to happen to Hubert Bird. But with the origin of his earlier isolation always lurking in the shadows, will he ever get to live the life he's pretended to have for so long?"--